2019
DOI: 10.1128/aem.01788-19
|View full text |Cite
|
Sign up to set email alerts
|

Genes Involved in Galactooligosaccharide Metabolism in Lactobacillus reuteri and Their Ecological Role in the Gastrointestinal Tract

Abstract: Strains of Lactobacillus reuteri are commonly used as probiotics due to their demonstrated therapeutic properties. Many strains of L. reuteri also utilize the prebiotic galactooligosaccharide (GOS), providing a basis for formulating synergistic synbiotics that could enhance growth or persistence of this organism in vivo. In this study, in-frame deletion mutants were constructed to characterize the molecular basis of GOS utilization in L. reuteri ATCC PTA-6475. Results suggested that GOS transport relies on a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…Not much is known about the mechanism of import and subsequent hydrolysis of GOS in L. plantarum, although a recent comparative transcription analysis of L. plantarum STIII revealed the GOS-growth induced upregulation of two gene clusters harboring various galactose- and lactose utilization genes, including lacS, lacA, lacL and lacM 23 . Similar genes were also identified to be involved in the utilization of GOS in L. reuteri ATCC PTA-6475 22 .…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…Not much is known about the mechanism of import and subsequent hydrolysis of GOS in L. plantarum, although a recent comparative transcription analysis of L. plantarum STIII revealed the GOS-growth induced upregulation of two gene clusters harboring various galactose- and lactose utilization genes, including lacS, lacA, lacL and lacM 23 . Similar genes were also identified to be involved in the utilization of GOS in L. reuteri ATCC PTA-6475 22 .…”
Section: Introductionmentioning
confidence: 68%
“…It remains to be established what the precise roles of LacA and LacLM in GOS hydrolysis are in L. plantarum (i.e., DP and branched or linear structure). Intriguingly, a recent investigation of GOS metabolism in L. reuteri ATCC PTA-6475 established a role of its LacA homologue (~ 37% identity with LacA in L. plantarum ) in hydrolysis of galactose-galactose linkages in GOS, but also showed that this enzyme could not hydrolyze lactose, which was dependent on the LacLM homologue in this species (~ 64% identity with L. plantarum ) 22 . Moreover, a LacS deficient L. reuteri derivative (~ 58% identity with L. plantarum LacS) displayed reduced growth efficiency on GOS as well as lactose, which is similar to the LacS mutant of L. plantarum in this study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, although our findings provide important basic information for the generation of hypotheses on the ecological role of pdu cluster, these hypotheses should be evaluated through in vivo experiments in relevant host systems using experimental designs similar to those utilized in our previous studies ( Duar et al, 2017 ; Lin et al, 2018 ; Cheng et al, 2020 ). Finally, pdu cluster functionality should be tested with additional carbohydrates that are therapeutically relevant, such as prebiotics ( Rattanaprasert et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the five strains, SRCM103571 and SRCM103689 possessed a number of unique genes including cscB, lacF_2, lacG, maa_1, nisB, nisC_2, sacA, and spaS, which are involved in disaccharide permeases, sucrose-5-phosphate hydrolase, nisin biosynthesis, and lantibiotic subtilin synthesis. Disaccharide metabolism-associated proteins including fructooligosaccharide and galactooligosaccharide permeases have been reported to be essential for colonization, have effects on cell membrane fluidity, and be required for prebiotic utilization, providing the bacterial strains to attach and colonize the host intestine [64][65][66]. Additionally, peptides such as nisin and subtilin, encoded by nisB, nisC, and spaS, are bacteriocin effective against many Gram-positive organisms, functioning as probable probiotics with antimicrobial activities [67][68][69].…”
Section: Comxmentioning
confidence: 99%